2020
DOI: 10.3390/ijms21082882
|View full text |Cite
|
Sign up to set email alerts
|

C5-Substituted 2-Selenouridines Ensure Efficient Base Pairing with Guanosine; Consequences for Reading the NNG-3′ Synonymous mRNA Codons

Abstract: 5-Substituted 2-selenouridines (R5Se2U) are post-transcriptional modifications present in the first anticodon position of transfer RNA. Their functional role in the regulation of gene expression is elusive. Here, we present efficient syntheses of 5-methylaminomethyl-2-selenouridine (1, mnm5Se2U), 5-carboxymethylaminomethyl-2-selenouridine (2, cmnm5Se2U), and Se2U (3) alongside the crystal structure of the latter nucleoside. By using pH-dependent potentiometric titration, pKa values for the N3H groups of 1-3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…This result allowed them to conclude that selenium-containing biomolecules are resistant to permanent oxidation, and this is the main reason for naturally occurring selenium in both 2-selenouridine- and Sec-containing proteins. This conclusion complementary to the latest data on the role of seleno modifications in tRNA ensuring the fidelity of the reading of synonymous 3′-G ending codons [ 19 ], prompted us to perform more detailed studies on the oxidation of 2-thiouracil (S2Ura) and 2-selenouracil (Se2Ura), especially in light of the recently discovered “oxidative desulfuration” of S2U, leading predominantly to 4-pyrimidinone derivatives [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionsupporting
confidence: 83%
“…This result allowed them to conclude that selenium-containing biomolecules are resistant to permanent oxidation, and this is the main reason for naturally occurring selenium in both 2-selenouridine- and Sec-containing proteins. This conclusion complementary to the latest data on the role of seleno modifications in tRNA ensuring the fidelity of the reading of synonymous 3′-G ending codons [ 19 ], prompted us to perform more detailed studies on the oxidation of 2-thiouracil (S2Ura) and 2-selenouracil (Se2Ura), especially in light of the recently discovered “oxidative desulfuration” of S2U, leading predominantly to 4-pyrimidinone derivatives [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionsupporting
confidence: 83%
“…[108] In 2020, Nawrot and co-workers described the synthesis of 5-methylaminomethyl-2-selenouridines and the study of their properties toward base pairing with guanosine. [109] Based on pH-dependent potentiometric titration, pKa values for the N3H groups of the synthetized selenouridines and their functional role were assessed. It was observed that in the physiological conditions, these compounds adopted preferentially the zwitterionic form.…”
Section: Incorporating the Selenium Moietymentioning
confidence: 99%
“…Selenol/diselenide exchange reactions were evidenced by the fact that, under the conditions used, i.e., in phosphate buffer with a pH of 7.4, about half of the selone 1 was deionized (p K a 7.30 [ 26 ]) and formed the selenolate anion I ( Figure 4 a). In the next step, the positively charged diselenide II reacted with selenolate I, forming the neutral form of diselenide 2 by exchange process (equilibrium reactions).…”
Section: Resultsmentioning
confidence: 99%
“…The observed chemical shift and line broadening were probably due to the deprotonation of selenol Se2U to selenolate form at pH 7.4, as its p K a was 7.30 and ca. was 50% in ionized form, in contrast to more acidic conditions [ 26 , 53 , 54 ]. Moreover, we can conclude that the exchange process between selenol/diselenide depends more on the buffer pH than on the temperature, as shown by the 77 Se NMR studies in water and at pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation